Standardization of Road Danger Signs in the European Union - Castelluccio, Francesco; Catalano, Mario; Fichera, Davide; Migliore, Marco; Amoroso, Salvatore (Promet - Traffic&Transportation, 2015)
The aim of this research is to find a solution for the standardization of road signs in the EU zone by a comparative analysis of different national sign systems to establish a common set from a single country. This work is based on the idea that road sign standardization might increase the safety level of transnational journeys and foster the relationships among the various members of the EU Community. This paper presents the outcome of the first step of the research, which focuses on the harmonization of danger signs. In more detail, a multicriteria approach is applied to rank 19 EU Member States on the basis of three main aspects: the installation cost of new signs, new sign learning issues and the effectiveness of sign systems. The study allows for the installation cost by quantifying the degree of similarity among road sign systems and the roadway network extension, on which new signs should be placed.